2022
DOI: 10.1007/s00280-022-04495-3
|View full text |Cite
|
Sign up to set email alerts
|

Moderate temperature reduction is sufficient for prevention of 5-fluorouracil-induced oral mucositis: an experimental in vivo study in rats

Abstract: Purpose The current idea of how oral mucositis (OM) develops is primarily based on hypotheses and the early events which precede clinically established OM remain to be demonstrated. Cryotherapy (CT) continues to have considerable promise in clinical settings to reduce chemotherapy-induced OM. Although being effective, the knowledge is scarce regarding the ideal temperature for prevention of OM. Thus, the present study had two main objectives: (i) to develop an animal model to investigate the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Further, moderate temperature reduction was su cient to reduce the early events which may precede clinically established OM. This could have clinical advantages in terms of tolerability [29].…”
Section: Discussionmentioning
confidence: 99%
“…Further, moderate temperature reduction was su cient to reduce the early events which may precede clinically established OM. This could have clinical advantages in terms of tolerability [29].…”
Section: Discussionmentioning
confidence: 99%
“…Further, moderate temperature reduction was sufficient to reduce the early events which may precede clinically established OM. This could have clinical advantages in terms of tolerability [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…This as the former resulted in a temperature reduction of 7.9 °C after 60 min of cooling [ 13 ], compared to 2.3 °C, and 3.7 °C in the present study for the intraoral mucosa as a whole and the non-keratinized areas, respectively. Although the differences in mean temperature reduction seems striking, in a recent in vivo study in rats [ 22 ] it was demonstrated that cooling to low temperatures (< 30 °C), which causes discomfort for the patient, may not be necessary to prevent OM. However, this is yet to be assessed in a clinical setting.…”
Section: Discussionmentioning
confidence: 99%